Adaptation of Foreign Pre-Graduate Students in the University Multicultural Educational Environment - NOVOSELOVA, Natalia; BONDAREVA, Veronika; SEMANINA, Anna; CHISTYAKOV, Alexander; ZETKINA, Alexandra (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article is devoted to the problem of cultural adaptation of foreign undergraduate students upon admission to study at master’s degree programs in Russian universities. The analysis of collected research data is performed based on the critical incident technique. The study involved conducting respondent interviews. The data obtained in the course of the study reveals the main indicators of stress, adaptation, and growth of communicative competence in various ethnic and cultural groups of respondentsRESUMEN El artículo está dedicado al problema de la adaptación cultural de estudiantes universitarios extranjeros al ingresar para estudiar en programas de maestría en universidades rusas. El análisis de los datos de investigación recopilados se realiza en función de la técnica de incidentes críticos. El estudio incluyó la realización de entrevistas a los encuestados. Los datos obtenidos en el curso del estudio revelan los principales indicadores de estrés, adaptación y crecimiento de la competencia comunicativa en varios grupos étnicos y culturales de encuestados.